2019
DOI: 10.1109/access.2019.2936682
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive State-of-the-Art Survey on the Transmission Network Expansion Planning Optimization Algorithms

Abstract: Long term planning in power transmission network expansion provides a well ordered and profitable extension of power equipment and facilities to meet the expected electric energy demand with an allowable degree of reliability. However, high quality and improved reliability in energy supply have to be balanced with the available funds. The need to expand transmission network can never be over emphasized. Transmission Network Expansion Planning (TNEP) is a periodical measure that must be carried out due to dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 162 publications
(160 reference statements)
0
12
0
1
Order By: Relevance
“…Its purpose is to provide a periodic power system expansion plan for the regional power load growth. On the basis of ensuring the transmission network reliability, it is still a major challenge to improve the reliability and quality of power supply by constructing new power equipment with minimize cost [12]. In addition, the TNEP task often regards about 10 years later as the target year, but most power operation data can only be obtained through prediction, which would bring huge uncertainty.…”
Section: A Summary Of Transmission Expansion Network Planningmentioning
confidence: 99%
“…Its purpose is to provide a periodic power system expansion plan for the regional power load growth. On the basis of ensuring the transmission network reliability, it is still a major challenge to improve the reliability and quality of power supply by constructing new power equipment with minimize cost [12]. In addition, the TNEP task often regards about 10 years later as the target year, but most power operation data can only be obtained through prediction, which would bring huge uncertainty.…”
Section: A Summary Of Transmission Expansion Network Planningmentioning
confidence: 99%
“…The indexes EENS and EWES are calculated in (25) and (26), respectively. These indexes are given in MWh/year and are obtained by the respective expected power in MW times the duration of 1 year (h/year), i.e., 8760 h.…”
Section: Performance Assessment (Step 7)mentioning
confidence: 99%
“…Reviews over TNEP challenges and optimization algorithms can be found in [3,24,25]. In [3], some gaps identified by the authors are presented and a methodology capable of dealing with TNEP under several levels of load and wind power is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of strategic power system planning is to meet future demand and integrate renewable energy sources (RES), with the restriction of being as reliable, economical, and environmentally friendly as possible [1]. These requirements result in many different optimization targets and planning problem formulations, as the exhaustive literature overviews show [2][3][4]. Standard industry practice in power system planning of distribution and sub-transmission grids is to manually design the power system based on a few hypothetical worst-casesituations [5].…”
Section: Introductionmentioning
confidence: 99%